Religious Identity, Terrorism, and Hybrid Insecurity in Northern Nigeria: Boko Haram, Banditry, and Civilian Targeting - Machibya, Lukuba; Priyanto, Sapto; Mahanakah, Omary (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This paper discusses trends of civilian killing in Northern Nigeria in terms of hybrid insecurity, as understood to be the intersection of ideologically driven jihadist insurgency with economically driven armed banditry under conditions of weak state control. The research targets Boko Haram and Islamic State West Africa Province (ISWAP) in the northeast and armed bandit groups in the northwest, where sectarian reasoning makes violence mainly a religious persecution problem. Based on the results of the qualitative analysis of peer-reviewed sources, datasets on conflict events, human rights reports, and documented incidences in the period between 2009 and 2025, the article proves that the phenomenon of civilian victimization is not incidental but is systematic and strategic. Although religious identity determines symbolic targeting and narrative framing, both Christian and Muslim civilians are disproportionately impacted by the cross-regional distribution. The results indicate that structural violence, institutional weakness, and relative deprivation permit the armed participants to instrumentalize identity via seeking territorial control, extracting resources, and replacing the government. The article makes a contribution to the study of terrorism by developing the concept of hybrid insecurity as an analytical tool capable of describing the crime terror nexus and showing the shortcomings of militarized counterterrorism in defending against civilians. It concludes that human security-minded interventions that focus on governance, accountability, and socioeconomic marginalization are needed to reduce sustained civilian casualties in Northern Nigeria